Entre a vida e a encenação: o novo realismo no cinema iraniano - Silvia Cristina de Paiva Pereira (2009)
This research investigates the emergence of a new realism in two works of contemporary Iranian cinema: Close-up (Abbas Kiarostami, 1990) and A moment of Innocence (Mohsen Makhmalbaf, 1996). Initially, we study the realism in cinema, emphasizing the Italian neo-realism and then we compare it with the Iranian´s experiences. Finally, we analyze the two movies, trying to demonstrate how they inaugurate a new form of realism, when they reappropriate, in a special way, an event that happened in real world.